2009
DOI: 10.1159/000201936
|View full text |Cite
|
Sign up to set email alerts
|

Worry Exposure versus Applied Relaxation in the Treatment of Generalized Anxiety Disorder

Abstract: Background: Worry exposure (WE) is a core element of cognitive-behavioral treatment for generalized anxiety disorder (GAD). Its efficacy as a stand-alone treatment method (without further cognitive-behavioral therapy interventions) has never been tested.We aimed to examine whether WE alone is as efficacious as the empirically supported stand-alone treatment for GAD, applied relaxation (AR). Methods: In a randomized controlled study, 73 outpatients meeting DSM-IV criteria for GAD as primary diagnosis were alloc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
93
1
7

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 130 publications
(108 citation statements)
references
References 54 publications
7
93
1
7
Order By: Relevance
“…In another RCT, guided imagery and progressive muscle relaxation was found to be most effective in enhancing levels of relaxation and decreasing heart rate. 107 Hoyer et al 108 compared worry exposure with applied relaxation in the treatment of GAD and results showed that the treatments were equally effective. However, a recent meta-analysis indicated that CBT may be more effective in treatment of GAD than applied relaxation.…”
Section: Relaxation Techniquesmentioning
confidence: 99%
“…In another RCT, guided imagery and progressive muscle relaxation was found to be most effective in enhancing levels of relaxation and decreasing heart rate. 107 Hoyer et al 108 compared worry exposure with applied relaxation in the treatment of GAD and results showed that the treatments were equally effective. However, a recent meta-analysis indicated that CBT may be more effective in treatment of GAD than applied relaxation.…”
Section: Relaxation Techniquesmentioning
confidence: 99%
“…[44,47] Cognitive avoidance does show some symptom specificity in adults with clinical worry when compared to panic symptoms [54] and also decreases with effective CBT treatment. [55,56] In children and adolescents there has been little investigation into the use of avoidant strategies but Gosselin et al [57] did show that nonclinical adolescents who experience high worry (N 5 158, Penn State Worry Questionnaire (PSWQ) M(SD) 5 61.2(6.2)) engage in more cognitive avoidance strategies than those experiencing moderate worry (N 5 187, PSWQ M(SD) 5 43.8(2.1)). Avoidant strategies significantly predicted worry level, with avoidance of triggers, thought substitution, distraction, and thought suppression accounting for 19% of the variance in the youths' worry scores.…”
Section: Dsm-iv Criterion A: the Nature Focus And Duration Of Anxiementioning
confidence: 99%
“…A lot of empirical work (i.e Rimm, 1979;Clark et al, 2003;Conrad &Roth, 2006;Goodwin &Montgomery, 2006;Hoyer et al, 2009) showed that muscle tension is related to anxiety and that an individual will experience comfort and decreased amount of anxiety if tense muscles can be made loose and comfortable. Relaxation is best when used within the context of self -management by the clients.…”
Section: Introductionmentioning
confidence: 99%
“…Further more Arakawa (1997) showed the efficacy of progressive muscle relaxation to reduce nausea, vomiting and anxiety induced by chemotherapy. Somewhat recently Hoyer et al (2009) investigated the efficacy of worry exposure and applied relaxation therapeutic techniques for the treatment of generalized anxiety disorder, while comparing with control group both were found to be effective.…”
Section: Introductionmentioning
confidence: 99%